ANALISIS PENGARUH FAKTOR EKSTERNAL DAN FAKTOR INTERNAL BANK TERHADAP NON PERFORMING FINANCING - Salsabilla, Annisa; Devia SS, Vietha (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
Non Performing Financing (NPF) is a ratio that shows the amount of financing problem on Islamic Bank. And increase in the NPF ratio of Islamic Bank will cause the bank’s health level and liquidity to decrease. This study aims to find out how external factors such as inflation and GDP, as well as bank internal factors such as Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), Operational Efficiency Ratio (BOPO), and Third Party Funds can affect changes in the ratio NPF. Islamic Bank can use this information as a reference for making regulations in anticipating an increase in the NPF ratio. This research focuses on Bank Muamalat Indonesia using the 2011-2020 quarter time period. This study uses a quantitative approach by conducting time series regression analysis to see the simultaneous and partial effects of the independent variables on the dependent variable. The results of this study indicate that inflation, GDP, CAR, FDR, BOPO, and Third Party Funds simultaneously have a significant effect on Bank Muamalat's NPF. Partially, inflation and BOPO have a significant positive effect, GDP and Third Party Funds have a significant negative effect, while CAR and FDR have no effect on Bank Muamalat's NPF